A strategy for continuous project innovation at Blue Dairy Corporation - Abanilla, J. Alberto L.; Cruz, Edison (Quezon City University of the Philippines Diliman, 2005)
Blue Dairy Corporation (BDC) is a Filipino corporation that caters to the quick service restaurant or fast food industry. Its major product lines are soft serve ice cream, ice cream toppings, syrups and processed vegetables. Its major client is McDonald's Philippines. In the past few years, sales to McDonald's have declined steadily. This was due to a reduction in the sales of soft serve sundae and the failure to introduce new products into the market to compensate for this decline. This paper is about a comprehensive strategy for continuous product innovation in BDC. The strategy created will be the roadmap towards creating a culture of product innovation in the company. Data was gathered thru interviews with present managers of the company, clients and other concerned parties. The macro industry trends will show the environment in which the company competes is rapidly changing. More direct and indirect competitors are present but a lot of opportunities remain for the company. However, the over-all sales picture of BDC shows a company in trouble. Its traditional business driver, soft serve ice cream, has declined significantly in sales thru the years. However, new stars are emerging from the syrups business. Chocolate fudge and caramel are growing at over 20 percent per year with secure competitive advantages. The processed vegetables volume is growing rapidly but its relative competitiveness is not clear due to the absence of appropriate data, which makes it a question mark. There is also the increasing trend towards more third party business sales over direct sales to McDonald's. The company has to lay the foundation for a culture of product innovation. These are having a product innovation champion, a dynamic R&D structure and resource allocation. Only when the foundation has been laid out will a successful execution of strategy happen. The key points of the recommended strategy are to shift the company innovation practice from its present user driven enhancement to being user-context development and to find new application driven innovations in the future. These can be done by understanding the market, creating strategic partnerships and stimulating new ideas.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Blue Dairy Corporation; Business planning; Strategic planning; Commercial products -- New products